Experimental analysis of atmospheric corrosion of steel S235JR in industrial environment - Stefanović Jelena N.; Mišković Zoran; Dimitrijević Stevan; Marković Zlatko; Spremić Milan (Hemijska Industrija)
The aim of this study was evaluation of atmospheric corrosion of structural steel S235JR in an industrial environment. General corrosion testing was carried out for six months in the field, at selected atmospheric corrosion stations, near the Sulphuric acid plant, in the Electrolytic refining plant and next to the automatic air quality monitoring station in the city of Bor, Serbia. The results were compared with the standard specimens stored in the laboratory. The steel S235JR specimens were characterized regarding mechanical characteristics by tensile testing. With the aim of assessing the mutual effect of corrosion and polluted industrial environment meteorological parameters were also determined, as well as pollutants in the atmosphere (mainly SO2). The X-ray diffraction method was used to identify the composition of corrosion products. Research within this work enabled a better understanding of the behavior of structural steel S235JR in which there was a reduction in load capacity due to corrosion. The corrosion rates obtained under each tested exposure condition showed noticeable differences. It was found that depending on the content of pollutants in the atmosphere and the location of the steel specimen, the corrosion products represented different compounds and solid phases.